LEXICAL AND SEMANTIC WAYS OF CONCEPT WAR VERBALIZING IN SPANISH JOURNALISTIC DISCOURSE - Drobiazko , Anna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article treats the investigation of the ways of linguistic foregrounding of the concept WAR, which, in connection with the tense socio-political events of the 21st century, occupies an important place in the consciousness of representatives of the Spanish-speaking society. In our opinion, further study of the ways of its understanding and interpretations in the mindset of each nation can be a significant contribution to the search for diplomatic ways of resolving armed conflicts all over the world. During the investigation we revealed the main ways of its representation in newspaper articles about Russian aggression against Georgia (2008) and Ukraine (2014, 2022). Texts of news feeds of Internet sources, Spanish-language periodicals and mass media were selected as material for analysis, as they best reflect the objective reality and represent an actual contemporary image of the war. Having considered the dictionary definitions of these lexemes-verbalizers, we investigated the conceptual component of the concept, examined the structural and semantic content of the concept. The contexts of the use of verbalizers were analyzed in order to determine the associative component, which helps to understand the attitude of producers and consumers of Spanish journalistic discourse towards this phenomenon. It has been established that the concept of WAR has an extensive nominative field and a wide range of interpretations depending on the context in which it is used. __________ References: • Broslavska, Ya. «Nominatyvnyi prostirkontseptu war / viina v amerykanskii movnii kartyni svitu [The nominative space of the concept of war in the American linguistic picture of the world].» Anhlistyka ta amerykanistyka 13 (2016): 27–32. • Vasyanovuch, «Ctrukturno-semantychne napovnennia kontseptu «VIINA» u linhvistychnykh doslidzhenniakh [Structural–semantic meaning of the “war” concept in linguistic researches].» Humanitarna osvita v tekhnichnykh vyshchykh navchalnykh zakladakh 38 (Kyiv, 2018): 5-9. • Golubovska, O. Etnichni osoblyvosti movnykh kartyn svitu [Ethnic features of language pictures of the world] (Kyiv: Logos, 2004), 282 p. • Danylych, S. Fenomen liudyny v systemi movy i kartyni svitu (za pamiatkamy epokhy stanovlennia natsionalnoi movy i natsionalnoi literatury Ispanii) [The phenomenon of man in the system of language and the picture of the world (according to the monuments of the era of the formation of the national language and national literature of Spain)] (Kyiv, 2000), 246. • Kaganovska, M. Tekstovi kontsepty khudozhnoi prozy: kohnityvna ta komunikatyvna dynamika (na materiali frantsuzkoi romanistyky seredyny 20 storichchia). (Dys. d-ra filol. nauk [Textual concepts of artistic prose: cognitive and communicative dynamics (on the material of French novels of the middle of the 20th century: Ph.D. Thesis)], Kyiv, 2003), 502. • Popova, M. Natsionalno-markovani kontsepty v movnii kartyni svitu Ispanii: dynamika rozvytku [Nationally marked concepts in the linguistic picture of the world of Spain: dynamics of development: monograph] (Kyiv, 2018), 268. • Yavorska Galina. «WAR concept: semantics and pragmatics [Kontsept «VIINA»: semantyka i prahmatyka].» Stratehichni priorytety1 (38) (2016): 14-23. • «A seis meses de la “operación militar especial” de Rusia en Ucrania, la guerra se eterniza.» El Observador (2022), https://www.elobservador.com.uy/nota/a-seis-meses-de-la-operacion-militar-especial-de-rusia-en-ucrania-la-guerra-se-eterniza-20228232260 • David, «Herszenhorn. La guerra de la desinformación.» El País (2014), https://elpais.com/internacional/2014/04/16/actualidad/1397671343_218418.html • EE UU desplegará tropas en la frontera oeste de Ucrania y Rusia mantiene las suyas en el este. 20 minutos internacional (2014), https://www.20minutos.es/noticia/2117108/0/ucrania/ tropas-occidente/rusia/ • «El ataque de Rusia a Ucrania: así ha empezado la guerra Madrid.» El País (2022), https://elpais.com/internacional/2022-02-24/video-asi-ha-empezado-la-guerra-en-ucrania.html • El Diccionario de la lengua española, https://dle.rae.es/ • Meyer, «Guerra relámpago en Georgia.» El País (2008), https://elpais.com/diario/ 2008/08/28/internacional/1219874407_850215.html • Lucía Abellán. «Rusia acepta una solución temporal a la ‘guerra del gas’.» El País (2014),https://elpais.com/internacional/2014/06/02/actualidad/1401736814_446491.html • Luis Doncellucía Abellán. «La ‘guerra del gas’ vislumbra su final.» El País (2014), https://elpais.com/internacional/2014/10/30/actualidad/1414701076_728776.html • María Antonia Sánchez Vallejo. La ofensiva de Kiev lleva la guerra al este. El País (2014), https://elpais.com/internacional/2014/05/03/actualidad/1399147310_358886.html • María, «Sahuquillo. Rusia lanza un ataque por tierra, mar y aire contra Ucrania y se acerca a la capital Sloviansk (Ucrania).» El País (2022), https://elpais.com/internacional/2022-02-24/putin-ordena-una-operacion-militar-en-ucrania.html • Rodrigo Fernández. «Guerra abierta entre Rusia y Georgia.» El Pais (2008), https://elpais.com/diario/2008/08/10/internacional/1218319201_850215.html • Rodrigo Fernández. «Rusia bombardea Georgia en una espiral de guerra abierta.» El País (2008), https://elpais.com/diario/2008/08/10/portada/1218319205_850215.html • Rodrigo Fernández. «Rusia inicia una ‘guerra del gas’ con cortes en el suministro a Ucrania.» El País (2014), https://elpais.com/internacional/2014/06/16/actualidad/1402905837_ html